Meninjau Ulang Candi Boyolangu sebagai Pendharmaan Gayatri Rajapatni - Yusuf, Muhamad Satok (AMERTA, 2024)
Abstract. The Re-interpretation of The Boyolangu Temple as The Place of Worship of Gayatri Rajapatni. This research attempts to criticize the experts’ debate on the location of Gayatri Rajapatni’s place of worship. Most experts identify this place as Boyolangu Temple in Tulungagung Regency, East Java. This research uses a qualitative descriptive approach involving data collection, processing, analysis, and interpretation. Comparative analysis was conducted on the Prajñāpāramitā statue in the Boyolangu Temple with the Siŋhasāri-style statue. Contextual analysis considers the context of the position of the river as a real and political boundary during the period of the Ancient Mataram and Siŋhasāri-Majapahit. The research findings indicate that two temples are dedicated to Rajapatni in different places and built at different times. The first temple, named Prajñāpāramitāpuri, was built in Kamal Pandak in 1287 Saka (1365 AD). The current location of Kamal Pandak is now Asem Kandang Village, Pasuruan Regency, downstream of the Brantas River. The temple structure has collapsed and has been converted into the tomb of Mbah Damarwulan. The second temple, named Wiśeṣapura at Bhayālangö, was built in 1291 Saka (1369 AD). The location of Bhayālangö is still preserved as the name of a village and sub-district in Tulungagung Regency, upstream of the Brantas River. Wiśeṣapura Temple in Bhayālangö is now known as Boyolangu Temple or Gayatri Temple. The construction of these two temples was a claim of King Hayam Wuruk’s hegemony to reunite the Java island, which had been divided into two kingdoms during the reign of King Airlangga. The discovery of the Prajñāpāramitā statue at Boyolangu Temple represents a Buddhist goddess statue from the Siŋhasāri period, transformed into a Rajapatni embodiment statue during the Majapahit era. Keywords: Boyolangu Temple, The Place of Worship of Rajapatni, Wiśeṣapura ri Bhayālangö, Transformation of Position, Prajñāpāramitā Statue   Abstrak. Penelitian ini berupaya mengkritisi perdebatan para ahli mengenai tempat pendharmaan Gayatri Rajapatni. Mayoritas ahli menyebut tempat tersebut sebagai Candi Boyolangu di Kabupaten Tulungagung, Jawa Timur. Penelitian ini menggunakan pendekatan deskriptif kualitatif, melalui proses pengumpulan, pengolahan, analisis, dan interpretasi data. Analisis perbandingan dilakukan terhadap arca Prajñāpāramitā di Candi Boyolangu dengan arca bercorak Siŋhasāri. Analisis kontekstual mempertimbangkan konteks kedudukan sungai sebagai pembatas nyata dan politis pada masa Mataram Kuno dan Siŋhasāri-Majapahit. Hasil penelitian menunjukkan bahwa terdapat dua candi pendharmaan Rajapatni di dua tempat berbeda dan dibangun pada waktu yang berbeda. Candi pertama bernama Prajñāpāramitāpuri yang didirikan di Kamal Pandak pada tahun 1287 S (1365 M). Lokasi Kamal Pandak sekarang menjadi Desa Asem Kandang, Kabupaten Pasuruan di hilir Sungai Brantas. Bangunan candi telah runtuh dan sekarang diubah menjadi makam Mbah Damarwulan. Candi kedua bernama Wiśeṣapura di Bhayālangö yang dibangun pada tahun 1291 S (1369 M). Lokasi Bhayālangö masih lestari menjadi nama desa dan kecamatan di Kabupaten Tulungagung, di hulu Sungai Brantas. Candi Wiśeṣapura di Bhayālangö sekarang dikenal sebagai Candi Boyolangu atau Candi Gayatri. Pembangunan dua candi tersebut sebagai klaim hegemoni Raja Hayam Wuruk untuk menyatukan kembali pulau Jawa yang pernah dibelah menjadi dua pada masa Airlangga. Adapun temuan arca Prajñāpāramitā di Candi Boyolangu merupakan arca dewi Buddhis dari periode Siŋhasāri yang ditransformasikan kedudukannya sebagai arca perwujudan Rajapatni pada masa Majapahit. Kata kunci:  Candi Boyolangu,  Pendharmaan  Rajapatni,  Wiśeṣapura  ri  Bhayālangö,  Transformasi Kedudukan, Arca Prajñāpāramitā